A series of alkaline earth metal coordination polymers constructed from two newly designed imidazole-based dicarboxylate ligands containing pyridinylmethyl groups. Issue 22 (22nd May 2017) - Cai, Song-Liang; He, Zi-Hao; Wu, Wan-Hua; Liu, Fang-Xiu; Huang, Xiao-Ling; Zheng, Sheng-Run; Fan, Jun; Zhang, Wei-Guang
Abstract : A series of alkaline earth metal CPs have been constructed from two newly designed imidazole-based dicarboxylate ligands, H3 p PyMIDC and H3 m PyMIDC. Abstract : Two new imidazole-based dicarboxylate ligands, which are 2-(pyridin-4-ylmethyl)-1 H -imidazole-4, 5-dicarboxylic acid (H3 p PyMIDC) and 2-(pyridin-3-ylmethyl)-1 H -imidazole-4, 5-dicarboxylic acid (H3 m PyMIDC), have been designed and successfully synthesized. Both these multidentate ligands are then used to react with different kinds of alkaline earth metal ions under solvothermal conditions, leading to the construction of a series of new coordination polymers (CPs), namely, [Ba(μ5 -H p PyMIDC)(H2 O)] n (1 ), [Sr(μ5 -H p PyMIDC)(H2 O)] n (2 ), [Ca2 (μ4 -H p PyMIDC)2 (H2 O)2 ] n (3 ), [Ca2 (μ3 -H p PyMIDC)(μ4 -H p PyMIDC)(H2 O)2 ]·H2 O n (4 ), [Ba(μ5 -H m PyMIDC)(H2 O)] n (5 ), [Mg10 (μ3 - m PyMIDC)3 (μ4 - m PyMIDC)3 (H2 O)21 ]·SO4 ·12H2 O n (6 ) and [Sr(μ2 -H2 m PyMIDC)2 (DMF)2 ] n ·H2 O n (7 ). Compounds1 and2 are isostructural, exhibiting two-dimensional (2D) network structures with a hexagonal honeycomb (6, 3) topology if the corresponding metal ions are seen as 3-connected nodes. Compound3 displays another type of 2D network, which is built by the connection of μ4 -H p PyMIDC ligands and Ca(ii ) centres. Compound4 is a binodal (3, 4)-connected 3D framework with the Schläfli symbol of (6·8 2 )(6 5 ·8). The 2D structure of compound5 is similar to those of compounds1 and2, although different kinds of ligands are employed. Compound6 exhibits an interesting 3D framework with apcu topology by considering each unusual heptanuclear magnesium cluster as a 6-connected node. In compound7, connection of μ2 -H2 m PyMIDC ligands with Sr(ii ) ions results in the formation of an uncommon 3D chiral framework containing two different types of 1D helical chains. The present results reveal that both these new imidazole-based dicarboxylate ligands containing flexible pyridinylmethyl groups show versatile coordination abilities and are good candidates for fabricating new CPs. Moreover, the thermogravimetric and solid-state luminescence properties of all the compounds have also been studied.